PERAN MODERASI PERCEIVED CORPORATE SOCIAL RESPONSIBILITY DALAM PENGARUH TRUST TERHADAP LOYALITAS DAN REPURCHASE INTENTION PADA AIR MINUM DALAM KEMASAN MEREK AQUA DI SURABAYA - Christina Esti Susanti (Journal of Management and Business Review, 2012)
In recent business competition, marketing managers try to satisfying consumers and building stable-long term relationship between company and consumer. The relationship needs consumer’s trust to company. That is why marketing managers are interested in knowing the impact of trust, loyalty and corporate social responsibility (CSR) toward customer retention (repurchase intention) in order to develop the long term profitability of the company. The long term relationship with consumers results in profitability and also impacts of survival and company development. In other word, trust influences toward loyalty and consumer retention. In the same moment, it is not surprising that academicians and practitioner effort to understand trust, customer loyalty, repurchase intention and CSR. This research examines firstly, influence of customer trust toward customer loyalty. Secondly, the research examines influence of customer loyalty toward repurchase intention. Thirdly, the research examines the role of perceived CSR as a moderating variable on the influence customer trust toward customer loyalty. The packaged-drinking water Aqua is taken as the research context because the Aqua company have donated 10 litter clean water in East Indonesia for each of one litter consumer buying. The result of the research shows that perceived CSR play a strong and positive role of influencing trust toward loyalty. Otherwise, trust influences strongly toward loyalty and loyalty influences strong enough toward repurchase intention. The result is expected to give managerial benefit for Aqua Company and also theoretical development in marketing related to the moderation role of perceived CSR in the influence of trust toward loyalty and repurchase intention.